Asian Children’s Literature and Film in a Global Age Local, National, and Transnational Trajectories - Wilson, Bernard; Gabriel, Sharmani Patricia (Asia-Pacific and Literature in English, 2020)
XXXIII, 398 p. 21 illus., 17 illus. in color.